Regularity in Daily Mood Stabilizer Dosage Taken by Patients with Bipolar Disorder - Bauer, M.; Glenn, T.; Alda, M.; Sagduyu, K.; Marsh, W.; Grof, P.; Munoz, R.; Baethge, C.; Lewitzka, U.; Pilhatsch, M.; Bauer, R.; Whybrow, P. C. (Pharmacopsychiatry, 2013)
The aim of this study was to investigate regularity in the daily mood stabilizer dosage taken by patients with bipolar disorder, and identify factors associated with irregularity.Self-reported daily mood and medication data were available from 206 patients who took the same mood stabilizer for ≥100 days. Approximate entropy (ApEn) was used to measure serial regularity in daily mood stabilizer dosage. Generalized estimating equations (GEE) were used to estimate if demographic or clinical variables were associated with ApEn.There was a wide range of regularity in the daily mood stabilizer dosage. The mean percent of days of missing doses was 13.6%. The number of psychotropic medications (p=0.007), pill burden (p=0.004) and percent of days with depressed mood (p=0.013) were associated with more irregularity, while the percent of days euthymic (p=0.014) was associated with less irregularity. The percent of days missing doses was not associated with the number of medications, pill burden or mood ratings.Patients may have irregularity in daily dosage in spite of a low percent of days missing doses. Psychotropic medication regimen complexity and depression are associated with increased dosage irregularity. Research is needed on how irregularity in daily dosage impacts the continuity of drug action of mood stabilizers.
Keywords: bipolar disorder; mood stabilizers; dosage